The Possible Explanation for Secondary Microseisms Seasonal and Annual Variations - Kalenda, P. (Pavel); Wandrol, I.; Holub, K. (Karel); Rušajová, J. (Jana) (2015)
Annual drift is typical for microseisms. We propose a model based on thermoelastic wave generation that explains the highest microseisms during winter using higher stress level at the same time. If we remove the average influence of the back¬ground stress from the microseisms, we obtain the residual microseisms, which show the semiannual periods with maxima in March and October. The histogram of anomalous microseisms has the same form as the variations in Length of the Day (LOD). This phenomenon is recognized as a secondary order mechanism after the annual drift. The synoptic situations and earthquakes were recognized as imminent triggers of anomalous microseisms. This synoptic situation is consistent with the uplift of the northern part of Europe after ice cap melting.